PELARANGAN PENGGUNAAN PRODUK HUAWEI DI AMERIKA SERIKAT BERDASARKAN NATIONAL DEFENSE AUTHORIZATION ACT (NDAA) 2019 - Setiawan, Endri; Yuniarti, Yuniarti; Tendy, Tendy (Department of International Relations, Universitas Mulawarman, 2023)
Huawei’s market development in the US are causing concern for the US Government. This led to it enacting NDAA 2019. This article aims to explain the premises of the enactment of the United States National Defense Authorization Act (NDAA) 2019 article 899 regarding the prohibition of the use of Huawei products. The type of research used in this research is explanative with secondary data types. The analysis technique used is qualitative. The theory used is the theory of Protectionism. The results of this study indicate that the 2019 ban on the use of Huawei products in the US based on the NDAA 2019 is based on three reasons. The first reason is the US desire to win the 5G market as an effort to protect the US cooperation in 5G development and to realize the US commitment as a world technology leader. The second reason is the alleged dumping and violation of Huawei's human rights, which can damage the value of the US domestic market and conflict with US national interests. The third reason is the insecurity of Huawei products due to the many violations committed by Huawei regarding intellectual property rights, espionage activities and trade agreement violations which are strong reasons for the implementation of the NDAA 2019.